A Review of the IELTS Test: Focus on Validity, Reliability, and Washback - Ali Hashemi; Samran Daneshfar (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
The International English Language Test System (IELTS) is one of the most reputable English tests that is used to assess the language proficiency of those who intend to study or work in an English speaking context. It is one of the most large-scale proficiency tests which affects the lives of many students, as well as immigrants as the results of the test, are used for making critical decisions about the test takers. Moreover, the process of designing a good test requires a clear understanding of both validity and reliability of the test format. Therefore, in the current paper, we try to offer a descriptive review of the IELTS test by concentrating on various issues such as reliability, validity and washback.